Advanced component transmission path analysis based on transmissibility matrices and blocked displacements. (22nd December 2018) - Liao, Xuhui; Li, Shunming; Yang, Shang-Kuo; Wang, Jinrui; Xu, Yong
Abstract: In component transmission path analysis (TPA), the blocked forces of subsystems and the frequency response functions (FRFs) of the total system need to be measured, which are always not easy to implement. In this paper, an advanced component TPA procedure is proposed. The method allows one to predict the vibroacoustic responses of coupled systems according to the dynamical properties of the subsystems. More specifically, it is based on the knowledge of the displacements of blocked subsystems and the transmissibility matrices between subsystems. The physical meanings of blocked displacements and transmissibility matrices are discussed in detail. It is proved that the transmissibility matrices in this method can be measured independently by suppliers of various components, which is important for complicated products' vibroacoustic response syntheses. Furthermore, an interpretation of this method's physical meaning is given in terms of the Neumann series. The response of a coupled system can be regarded as the result of the superposition of infinite transmissions. This highlights the transmission mechanism of vibration and makes the method more perceivable. The method is illustrated and validated by a numerical model and a finite element (FE) model. Highlights: A novel method for predicting the responses of coupled structures is proposed. The physical meaning of this method is interpreted. Coupling problems are illustrated and visualized by means of Neumann series. The characteristics of transmissibility matrices are addressed in detail. The method is illustrated and validated by two examples.